Saliva pH Between Gargling and without Gargling Water after Consuming Sweet and Sticky Foods - Siti Sulastri; Herastuti Sulistiyani; Furaida Khasanah (JURNAL INFO KESEHATAN, 2021)
Sweet and sticky foods are the main energy source for oral bacteria and are directly involved in lowering the pH. Gargling with boiled water after every meal can speed up the pH of the saliva in the mouth to return to normal. The objective of this study is to determine the difference in salivary pH between gargling and without gargling water after consuming sweet foods in elementary school students. The research method used was quasi-experimental with pretest and posttest with control group design. The instrument in this research was a pH meter. The population in this study were students in grades I – V of public elementary schools in Bantul with a total population of 135. The research sample used total sampling. Analysis of the research data was conducted using the Wilcoxon test, Mann Withney and Anova Test. The results showed that the pH of saliva (direct gargling) of water/0 minutes after consuming sweet and sticky foods was before 7.53 after gargling 7.99 increased by 0.46. The pH of gargling saliva 5 minutes before 7.48 after rinsing 7.63 increased 0.15. pH of saliva gargling 10 minutes, that was before 7.31 after gargling 7.3 decreased by 0.18. pH of saliva (without rinsing) water/0 minutes, which was initial pH 7.68 to 7.55 after consuming sweet and sticky foods, decreased 0 ,13. The pH of saliva without rinsing with water for 5 minutes, the initial pH was 7.70 to 7.06, decreased by 0.64. The most effective gargling time on salivary pH was gargling water immediately 0 minutes after consuming sweet and sticky foods. The time without gargling water affecting the pH of saliva after consuming sweet and sticky foods was 5 minutes.